Culture, tourism, and territory: Analyzing discourses and perceptions of actors in Byblos and Baalbek in Lebanon. Issue 6 (2nd November 2021) - Chaddad, Rita
ABSTRACT: Lebanon is a laboratory of cultural and territorial mobilities. The civil war caused the emergence of communal cultures and diverse modalities of locals/visitors encounters dependent on locals' religions and visitors' origins, and to the submission of territorial development to geopolitical interventions. This paper focuses on an empirical approach that determines cultural dynamics, tourism encounters, and mobilities as fundamental pillars of territory development in two Lebanese cities with different religious backgrounds, Christian in Byblos and Muslim in Baalbek. The discursive analysis of documentation reveals the focus of local, national, and international actors in both cities on the valorization of archaeological sites with the inclination of the local actors towards inclusive development. 264 and 245 qualitative surveys distributed to locals and visitors in Byblos and Baalbek respectively and analyzed statistically disclose their perceptions oriented primarily towards cultural tourism, with leisure tourism emerging in Byblos and religious tourism prospering in Baalbek. The discourses of multilevel actors and the surveys reveal that the degree of consensus between actors, locals, and visitors on cultural, touristic, and territorial dimensions is more significant in Byblos than in Baalbek. This paper points out the impacts of locals' religions, locals/visitors encounters, and geopolitical issues on the mobilization of territories.